Autumn Sun - Mignogna, Eduardo; Camorino, Marcelo; Aleandro, Norma; Luppi, Federico; Luz, Jorge (Pathé, 2005)
Set in Buenos Aires, "Autumn Sun" takes an earnest and warm look at romance among seniors, proving that it’s never to late to fall in love. Norma Aleandro shines in her San Sebastian Best Actress award-winning role as Clara Goldstein, a middle-aged Jewish woman who turns to the personal ads in order to find herself a mate before her brother's visit. A lover of tap-dancing to Fred Astaire songs and the sizzling chemistry found in old movies starring Bogie and Bacall, Clara finally meets Raoul, a kind and patient senior who takes to our leading lady right away. However, once she learns that Raoul (Federico Luppi) is a Gentile, she dashes any chance of real romance and instead enlists his help in posing as her fiance, privately tutoring her new beau in the ways of Judaism. Of course, during the crash course in culture in Clara's own version of Hebrew school, the two manage to fall in love but instead of in the similarly themed sitcom styled American film, "Picture Perfect", "Autumn Sun" is moving and sincere with an emotional, heartbreaking twist near the end that packs a wallop and like Clara, makes a romantic believer out of anyone. [reviews.filmintuition.com]